Particle transport of U-234-U-238 in the Kalix River and in the Baltic Sea - Andersson, P; Porcelli, D; Wasserburg, G; Ingri, J (1998)
The role of particles for U isotope transport was investigated in the Kalix River watershed, a particle-poor, Fe/Mn-rich river in northern Sweden, and in the Baltic Sea estuary. Particles >0.45μm are strongly enriched in U and contain 20-50% of the total riverine uranium budget and <1% of the total U in brackish waters (3-7 PSU). The particles have high δ234U which is close to that of dissolved U in the associated water, indicating that U on particles is dominantly nondetrital and isotopically exchanges rapidly with the ambient dissolved U. Particles at the river mouth are dominated by nondetrital Fe-Mn oxyhydroxides. Uranium and Fe are strongly correlated, clearly demonstrating that secondary Fe-oxyhydroxide is the major carrier of U in river water. There is no evidence for significant association of U with Mn-oxyhydroxide. Apparent U distribution coefficients (K̂Fed) were calculated for U between the authigenic Fe on particles and the solution. These values appear to be relatively constant throughout the year. This suggests an equilibrium between Fe in solution and authigenic Fe-oxyhydroxides on detrital particles. High values of K̂Fed calculated for one summer as well as high U concentrations in brackish waters can be explained by U scavenging by biogenic phases with low authigenic Fe content. Copyright © 1998 Elsevier Science Ltd.